2023
DOI: 10.7759/cureus.35725
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of the Impact of COVID-19 on Kidney Transplant Patients in the United States

Abstract: SARS-CoV-2, responsible for the COVID-19 pandemic, is a highly infectious virus that quickly became and continues to be a public health emergency, given the severe international implications. Immunocompromised patients, such as those undergoing kidney transplantation, are at an increased risk for severe illness from COVID-19 and require hospitalization for more aggressive treatment to ensure survival. COVID-19 has been infecting kidney transplant recipients (KTRs), affecting their treatment protocols, and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(119 reference statements)
1
0
0
Order By: Relevance
“…The COVID-19 code was recorded in 26 out of the 2444 KTs performed in 2020, being found in 6 of the 39 patients deceased that year (15.38%) and in 0.83% of the survivors. These findings reflect the previously demonstrated association between IHM and COVID-19 in KT recipients 11 12 43 44…”
Section: Discussionsupporting
confidence: 91%
“…The COVID-19 code was recorded in 26 out of the 2444 KTs performed in 2020, being found in 6 of the 39 patients deceased that year (15.38%) and in 0.83% of the survivors. These findings reflect the previously demonstrated association between IHM and COVID-19 in KT recipients 11 12 43 44…”
Section: Discussionsupporting
confidence: 91%
“…This can lead to more severe disease progression and higher mortality rates. 22 A study by Wu et al found that the median time from symptom onset to diagnosis was longer in kidney transplant recipients with COVID-19 than in non-transplant patients with COVID-19. 23 The vaccination rate among renal transplant recipients in our study was observed to be 21%, markedly lower than the reported national coverage in China, which stood at 89.54% for full vaccination and 91.89% for at least one dose as of February 2023.…”
Section: Discussionmentioning
confidence: 99%